2003
DOI: 10.1152/ajprenal.00134.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress and heme oxygenase activity in morphine-induced glomerular epithelial cell growth

Abstract: Opiate addiction has been reported to contribute to the progression of renal injury. In addition, opiate addiction is a major risk factor for the development of human immunodeficiency virus-associated nephropathy. In the present study, we evaluated the effects of morphine, an active metabolite of heroin, on glomerular epithelial cell (GEC) growth and the involved molecular mechanism. At lower concentrations, morphine promoted GEC proliferation; however, at higher concentrations, morphine triggered apoptosis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 46 publications
(38 reference statements)
3
27
0
3
Order By: Relevance
“…Morphine has a bimodal effect on GEC (190). At lower concentrations, morphine promotes GEC growth, whereas at higher concentrations, morphine triggers GEC apoptosis.…”
Section: Direct Effects Of Heroin/morphine On the Kidney: Pathophysiomentioning
confidence: 99%
“…Morphine has a bimodal effect on GEC (190). At lower concentrations, morphine promotes GEC growth, whereas at higher concentrations, morphine triggers GEC apoptosis.…”
Section: Direct Effects Of Heroin/morphine On the Kidney: Pathophysiomentioning
confidence: 99%
“…Higher concentrations of morphine triggered glomerular epithelial cell apoptosis. Free-radical scavengers as well as antioxidants inhibit morphine-induced pro-apoptotic effects, suggesting that the effects of morphine are mediated through oxidative stress [57]. A recent study showed that morphine increases intestinal ulcer formation and degradation of the host defense barrier.…”
Section: Physical Barriers: Epitheliamentioning
confidence: 99%
“…Other studies linking opiates to oxidative stress focus on the determination of reactive oxygen species (ROS) in white blood cells (1), superoxide (17)(18)(19) or markers of oxidative damage such as malondialdehyde (MDA) (13,20,21), thiobarbituric acid reactive substances (TBARS), tissue carbonyl content (1,13) and isoprostane (3). Nevertheless, there is, to our knowledge, limited work on the evaluation of oxidative balance, as a whole, in heroin addicted individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is also implicated, as an underlying mechanism, in heroin-induced hepatotoxicity (27), as well as in the pathogenesis of renal lesions, such as focal and segmental glomerulosclerosis, secondary to heroin abuse (17,19,28). Researchers have even concluded that antioxidants can prevent the formation of such lesions.…”
Section: Discussionmentioning
confidence: 99%